2011
DOI: 10.1371/journal.pone.0021080
|View full text |Cite
|
Sign up to set email alerts
|

Informational Gene Phylogenies Do Not Support a Fourth Domain of Life for Nucleocytoplasmic Large DNA Viruses

Abstract: Mimivirus is a nucleocytoplasmic large DNA virus (NCLDV) with a genome size (1.2 Mb) and coding capacity ( 1000 genes) comparable to that of some cellular organisms. Unlike other viruses, Mimivirus and its NCLDV relatives encode homologs of broadly conserved informational genes found in Bacteria, Archaea, and Eukaryotes, raising the possibility that they could be placed on the tree of life. A recent phylogenetic analysis of these genes showed the NCLDVs emerging as a monophyletic group branching between Eukary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 50 publications
5
65
0
Order By: Relevance
“…For example, a viral fourth domain sister to the eukaryotes has been proposed based on the phylogeny of clamp loader proteins [66] and of the RNA polymerase II (RNAP2), transcription factor II beta, flap endonuclease and proliferating cell nuclear antigen [28]. As in the previous cases, subsequent analyses of those datasets using more robust methods and sequence evolution models as well as more comprehensive taxonomic samplings demonstrated once again that the giant virus sequences were misplaced in the original analyses because of their high evolutionary rate and/or compositional bias and that, actually, these genes had most likely been acquired by the viruses from eukaryotic donors [67,68]. In §5, we revisit one of these examples in more detail.…”
Section: Giant Viruses Horizontal Gene Transfer and Long Branch Attrmentioning
confidence: 83%
See 2 more Smart Citations
“…For example, a viral fourth domain sister to the eukaryotes has been proposed based on the phylogeny of clamp loader proteins [66] and of the RNA polymerase II (RNAP2), transcription factor II beta, flap endonuclease and proliferating cell nuclear antigen [28]. As in the previous cases, subsequent analyses of those datasets using more robust methods and sequence evolution models as well as more comprehensive taxonomic samplings demonstrated once again that the giant virus sequences were misplaced in the original analyses because of their high evolutionary rate and/or compositional bias and that, actually, these genes had most likely been acquired by the viruses from eukaryotic donors [67,68]. In §5, we revisit one of these examples in more detail.…”
Section: Giant Viruses Horizontal Gene Transfer and Long Branch Attrmentioning
confidence: 83%
“…2 in [28]). In a detailed reanalysis of this marker, Williams et al [68] demonstrated that the RNAP2 sequence dataset contained a substantial amount of non-phylogenetic signal, mainly owing to the high evolutionary rate and compositional bias of the viral sequences. They also showed the very poor fit between the sequence data and the JTT model and verified that more complex models exhibited significantly better fit.…”
Section: Giant Viruses Caught In the Felsenstein's Trapmentioning
confidence: 99%
See 1 more Smart Citation
“…As we will see, while some of these ideas fall under the two rival views on the nature and origin of life (metabolism versus genetic information) and cannot be properly tested, others can be tested by using appropriate molecular phylogenetic analyses and, in most cases, refuted (López-García and Moreira 2009; Moreira 2000; Moreira and López-García 2009; Williams et al 2011). At any rate, these different heterogeneous models have stimulated virocentric debates, which can be classed as two types.…”
Section: Novel Virocentric Hypothesesmentioning
confidence: 99%
“…It is therefore essential to include sequences from the virus' hosts or host family to see whether or not the viral sequence places close to them. Using better taxon sampling and adequate models of sequence evolution, it can be shown that the vast majority of homologues to cellular genes present in giant viruses correspond to transfers from the host (or from bacteria co-infecting the same host) to its virus; and that NCLDV genes do not form a monophyletic group at the base of eukaryotes, but appear dispersed within the eukaryotic tree close to their respective hosts Moreira 2000;Moreira and Brochier-Armanet 2008;Moreira and Lopez-Garcia 2005;Moreira and López-García 2009;Williams et al 2011). Therefore, the hypothesis that NCLDV giant viruses form a fourth domain of life that can be placed in an organismal tree of life (Boyer et al 2010;Raoult et al 2004) can be refuted.…”
Section: Do Some Giant Viruses Form a Fourth Domain Of Life?mentioning
confidence: 99%